Effect of composition and nanostructure on the mechanical properties and thermal stability of Zr100-xCux thin film metallic glasses. (July 2022) - Brognara, Andrea; Best, James P.; Djemia, Philippe; Faurie, Damien; Dehm, Gerhard; Ghidelli, Matteo
Graphical abstract: Highlights: The mechanical properties and thermal stability of nanostructured columnar Zr100-x Cux thin film metallic glasses were investigated and compared to those of homogeneous films. Crystallization temperature, hardness and elastic modulus were found to be mostly dependent on composition and local atomic order rather than from film nanostructure. Viscoplastic behavior show high influence on both film composition and nanostructure, with columnar Zr-rich films showing higher tendency toward serrated flow deformation. Resistance to cracking is higher for Cu-rich and homogeneous films thanks to the higher density of full icosahedral atomic packing, while interfaces favored crack initiation. Abstract: Thin film metallic glasses (TFMGs) are a novel class of materials showing a mutual combination of large plastic deformation in tension (>10% strain) and superior yield strength up to ∼ 3.5 GPa, which make them ideal candidates for applications such as flexible electronics. Nevertheless, a clear relationship between the atomic structure and mechanical properties of TFMGs has not yet been achieved. In particular, the role of composition in determining a different local atomic order and the effect of nanostructure on TFMGs properties must be further investigated. In this work, the mechanical properties and thermal stability of several amorphous Zr100-x Cux TFMGs with either compact or fine columnar nanostructure were studied. The mediating role of composition in controlling crystallization temperature and hardness is here reported, which was found to increase from 4.6 to 7.7 GPa with increasing Cu content from 26 to 76 at.%. Moreover, plastic behavior and fracture resistance are shown to be highly dependent on both composition and nanostructure, with the Cu-rich and homogeneous film able to withstand elongation up to 2% strain before crack initiation. These results underline how atomic structure changes induced by composition can effectively influence TFMG properties, while demonstrating an approach to tune their behavior for various technological applications.